Classical Swine Fever in a Cuban Zone Intended for Eradication: Spatiotemporal Clustering and Risk Factors - Fonseca-Rodríguez, Osvaldo; Centelles García, Yosdany; Alfonso Zamora, Pastor; Ferrer-Miranda, Edyniesky; Montano, Damarys de las Nieves; Blanco, Miriam; Gutiérrez, Yobani; Calistri, Paolo; Santoro, Kleber Régis; Percedo, María Irian (Frontiers in Veterinary Science, 2020)
Classical Swine Fever (CSF) is an endemic disease in Cuba, and an eradication strategy by zones is planned by the Official Veterinary Service. The aim of this study was to identify high-risk areas of CSF and the risk factors associated with the disease occurrence in the Pinar del Río province, one of the prioritized areas in the eradication strategy. The outbreak occurrence at district level was analyzed through a 7-year period (2009 to 2015). A high-risk cluster (RR = 5.13, 95% CI 3.49–7.56) was detected during the last 2 years of the study period in the eastern half of the province, with 38 out of 97 districts included. The rate of CSF-affected holdings had a significant increase during 2014–2015 and seems to have occurred mainly in the high-risk cluster area. Swine population density by district (heads/km2) and road length (km) by district were associated with the disease outbreak occurrence. These results provide new insights into the knowledge of the epidemiology of the disease in Cuban endemic conditions and can contribute to improving the control and the eradication strategy in this situation.